Intermittent fault diagnosis in dynamic topology MANETs. (2015) - Sahoo, Manmath Narayan; Khilar, Pabitra Mohan
The application of Mobile Ad hoc Networks (MANETs) in critical activities like military scenarios and rescue operations mandates it to be fault-free and reliable. This paper presents a flexible Distributed Self Diagnosis Protocol (DSDP) considering the time-varying topology of MANETs. Both hard and soft faulty mobile hosts are to be diagnosed. Again, two variants of soft faults are considered, namely, permanent and intermittent faults. The proposed flexible-DSDP is developed on the top of comparison based diagnostic model, where the outcomes of the same test task executed by neighbouring hosts are compared. The hosts are diagnosed as fault-free or faulty based on the matching or mismatching results of the comparisons. Analytically, the proposed protocol is proved to be correct and complete. The validity of the proposed DSDP is supported with the accuracy and false alarm rates obtained through simulation.